Clinical characteristics and mutation spectrum of GLA in Korean patients with Fabry disease by a nationwide survey: Underdiagnosis of late-onset phenotype. Issue 29 (July 2017) - Choi, Jin-Ho; Lee, Beom Hee; Heo, Sun Hee; Kim, Gu-Hwan; Kim, Yoo-Mi; Kim, Dae-Seong; Ko, Jung Min; Sohn, Young Bae; Hong, Yong Hee; Lee, Dong-Hwan; Kook, Hoon; Lim, Han Hyuk; et al.
Abstract : Abstract: Fabry disease is a rare X-linked lysosomal storage disorder caused by an α-galactosidase A deficiency. The progressive accumulation of globotriaosylceramide (GL-3) results in life-threatening complications, including renal, cardiac, and cerebrovascular diseases. This study investigated the phenotypic and molecular spectra of GLA mutations in Korean patients with Fabry disease using a nationwide survey. This study included 94 patients from 46 independent pedigrees: 38 adult males, 46 symptomatic females, and 10 pediatric males. Each diagnosis was based on an enzyme assay and GLA gene mutation analysis. The mean age at presentation was 24 years (range, 5–65 years); however, the diagnoses were delayed by 21 ± 19 years after the onset of symptoms. Those patients with late-onset Fabry disease were diagnosed by family screening or milder symptoms at a later age. Forty different mutations were identified: 20 missense (50%), 10 nonsense (25%), 8 frameshift (20%), and 2 splice site (5%) mutations. Five of them were novel. IVS4+919G>A (c.936+919 G>A) was not detected among the 6505 alleles via newborn screening using dried blood spots. Enzyme replacement therapy (ERT) was performed in all the males and pediatric patients, whereas 75% of the symptomatic females underwent ERT for 4.2 ± 3.6 years. This study described the demographic data, wide clinical spectrum of phenotypes, and GLA mutation spectrum of Fabry disease in Korea. Most of the patients had classical Fabry disease, with a 4 times higher incidence than that of late-onset Fabry disease, indicating an underdiagnosis of mild, late-onset Fabry disease. Abstract : Supplemental Digital Content is available in the text